If Goa is your land, which are your stories? Narrating the Village, Narrating Home (Gragoatá, 2016)
Goa, India, is a multicultural community with a broad archive of literary narratives in Konkani, Marathi, English and Portuguese. While Konkani in its Devanagari version, and not in the Roman script, has been Goa’s official language since 1987, there are many other narratives in Marathi, the neighbor state of Maharashtra, in Portuguese, legacy of the Portuguese presence in Goa since 1510 to 1961, and English, result of the British colonization of India until 1947. This situation already reveals that there is a relationship among these languages and cultures that at times is highly conflictive at a political, cultural and historical level. In turn, they are not separate units but are profoundly interrelated in the sense that histories told in one language are complemented or contested when narrated in the other languages of Goa. One way to relate them in a meaningful dialogue is through a common metaphor that, at one level, will help us expand our knowledge of the points in common and cultural and literary differences among them all. In this article, the common metaphor to better visualize the complex literary tradition from Goa will be that of the village since it is central to the social structure not only of Goa but of India. Therefore, it is always present in the many Goan literary narratives in the different languages though from perspectives that both complement and contradict each other.----------------------------------------------------------------------------------------------------Se Goa é a sua terra, quais são suas histórias? Narrando o vilarejo, narrando o larGoa, Índia, é uma comunidade multicultural com um vasto arquivo de narrativas em concani, marata, inglês e português. Enquanto o concani, na sua versão em devanagari, e não no alfabeto romano, é a língua oficial de Goa desde 1987, há também muitas narrativas em marata, a língua do estado vizinho de Maharastra, em português, o legado da presença portuguesa em Goa desde 1510 até 1961, e em língua inglesa, resultado da colonização britânica da Índia até 1947. Essa situação já revela que a relação entre essas línguas e culturas é muitas vezes conflituosa em nível político, cultural e literário. Por sua vez, elas não são unidades separadas, mas estão profundamente relacionadas no sentido que histórias contadas em uma língua são complementadas ou contestadas quando narradas em outra das línguas de Goa. Uma maneira de relacioná-las em um diálogo significativo é através de uma metáfora em comum que nos ajude a expandir o nosso entendimento das afinidades e diferenças culturais e literárias em Goa. Neste artigo, a metáfora em comum para melhor visualizar a complexa tradição literária goesa, nas suas diferentes línguas, será a do vilarejo uma vez que esse tipo de comunidade é central na estrutura social não somente de Goa, mas da Índia e, por isso, sempre está presente em muitas narrativas literárias, embora de perspectivas, ora complementares, ora contraditórias.---Artigo em inglês.